1942. Effect of SARS-CoV-2 Vaccination in a Frailty COVID-19 Cohort: a Real Life Experience in a Northern Italy Hospital. (15th December 2022) - Russo, Chiara; Tagliafico, Luca; Labate, Laura; Ponzano, Marta; Mirabella, Michele; Portunato, Federica; Bellezza, Carmen; Mora, Sara; Arboscello, Eleonora; Nencioni, Alessio; Giacomini, Mauro; Dentone, Chiara; et al.
Abstract: Background: Clinical trial demonstrated that SARS-CoV-2 vaccines have the ability of reduce mortality and morbidity due to COVID-19. The aim of this study is to describe the effect of vaccination in term of mortality, type of ventilation and ICU admission among patients hospitalized for COVID-19 from May to December 2021 in a Ligurian Hospital. Methods: This is a retrospective, single-center study conducted in San Martino Hospital (Genoa, Italy), including patients ≥ 18 years hospitalized for COVID-19 in Infectious Disease and Emergency Units from 1 st May to 31 st December 2021. We collected demographical data, multimorbidity and disability score, vaccination time ("vaccinated" all patients hospitalized ≥ 14 days after first dose or ≥ 7 days after second/third dose), therapy for COVID-19, mortality at 7 and 30 days, ICU admission, ventilation type. Characteristics of vaccinated (group A) versus non vaccinated (group B) patients were compared using Chi-squared/Fisher's exact test for categorical variables and t-test /Kruskal-Wallis test for the continuous ones. Cox proportional hazards models for death at 30 days were performed as univariate analysis as well as adjusting for age, Cumulative Illness Rating Scale [CIRS], gender, Remdesivir, Monoclonal antibodies, Tocilizumab use. Results: Overall, 405 patients SARS-CoV-2 infected were enrolled. Data about timing of vaccination were available for 360 patients (89%). We compared clinical characteristics and outcomes of group A (32%) versus group B (68%). In group A patients were older (p< 0.001) and frailer (higher CIRS score and lower Barthel index, p< 0.001) than in group B. Among patients requiring oxygen, 76 (31.5%) in group B vs 26 (22.41%) in group A needed high flow ventilation (p=0.036); 33 (13.52%) vs 3 (2.59%) respectively were admitted to ICU (Figure 1). Mortality at 30 days after hospitalization was higher in group A at univariate analysis [HR(95%CI) 1.44(0.82; 2.53), p=0.208], lower at multivariate analysis [0.57(0.31; 1.02), p=0.059]. Conclusion: The results of this study confirm that SARS-CoV-2 vaccination reduces rate of admission to ICU and 30 days mortality among patients hospitalized for COVID-19. In our cohort mortality among vaccinated patients remains high and we hypothesized this is due to high frailty of evaluated population. Disclosures: Chiara Dentone, CD, Angelini: Advisor/Consultant|Gilead: Advisor/Consultant|Menarini: Advisor/Consultant|Novartis: Advisor/Consultant Matteo Bassetti, PhD, Angelini: Advisor/Consultant|Astellas: Grant/Research Support|Bayer: Advisor/Consultant|Bayer: Honoraria|BioMe ́ rieux: Advisor/Consultant|BioMe ́ rieux: Honoraria|Cidara: Advisor/Consultant|Cidara: Honoraria|Cipla: Advisor/Consultant|Cipla: Honoraria|Gilead: Advisor/Consultant|Gilead: Honoraria|Menarini: Advisor/Consultant|Menarini: Honoraria|MSD: Advisor/Consultant|MSD: Honoraria|Nabriva: Advisor/Consultant|Pfizer: Advisor/Consultant|Pfizer: Board Member|Pfizer: Grant/Research Support|Pfizer: Honoraria|Shionogi: Advisor/Consultant|Shionogi: Honoraria|Tetraphase: Advisor/Consultant.